Synthesis, characterization and biological activity study of some new palladium(II) complexes containing amine or azomethine groups - Al-Fregi, Adil Ali; Al-Fadhly, Ahmed Laith; Al-Salami, Bushra Kamel (European Journal of Chemistry, 2017)
This study reports the preparative methods of two types of palladium(II) complexes. The first method revealed two newly palladium (II) complexes derived from bidentate amine ligands, and the second one describes six newly palladium(II) complexes derived from bidentate Schiff base ligands. All the synthesized complexes have been characterized by elemental analysis, conductivity measurements, UV-Visible, FT-IR and 1H NMR spectral data. In vitro, all the synthesized complexes have been tested for their growth inhibitory activity against Gram negative bacteria Escherichia coli and Gram positive Staphylococcus aureus as well as determining the minimum inhibitory concentration. In addition, the interactions between compounded complexes and human DNA were also studied.